A battery with sulphur cathode and lithiated graphite anode based on Lithium shuttle reaction. (28th July 2016) - Xu, Feng; Li, Xiang; Xiao, Fei; Xu, Shengzhao; Zhang, Xueping; He, Ping; Zhou, Haoshen
Abstract: Current commercial Li-ion batteries cannot meet the requirement of electric vehicles for long-distance transportation due to the limitation capacity of cathodes materials. Sulphur is a promising candidate as its theoretical specific capacity is as high as 1675 mAh g −1 . In this work, a design of new Li-ion battery is reported. Electrochemical method is applied to prelithiate graphite, and the anode is coupled with sulphur cathodes to assemble the corresponding cell. The cell shows a high initial charge capacity of 1113 mAh g −1 at 0.2C and obtains a large specific energy of 485 Wh kg −1 . Also, prelithiated sulphur (Li2 S) is able to assemble Li2 S/graphite cell. The cell reaches 1226 mAh g −1 in the first charge process and the specific energy is as large as 390 Wh kg −1 . Both cells show large specific energy and have considerable potential for practical application.